2011
DOI: 10.1111/j.1755-5922.2011.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

An Old Friend in a New Light: The Role of Osteocalcin in Energy Metabolism

Abstract: SUMMARYAccumulating evidence suggests interactions between bone and energy metabolism, which may affect the risk of cardiovascular disease. Recent animal studies indicate that osteocalcin (OC) plays a key role in the coordinated regulation of glucose and insulin metabolism while insulin receptors on osteoblasts may regulate bone turnover and circulating OC levels. Association studies, weight loss interventions, and observational data lend some support to the existence and relevance of these mechanisms in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
32

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 136 publications
(185 reference statements)
0
9
0
32
Order By: Relevance
“…Certainly, confirmation through changes in multiple bone formation markers would be consistent with the known effects of insulin on the osteoblast. 12 In fact, in mice, insulin signalling stimulates the synthesis not only of osteocalcin but also of other major matrix proteins, as well as MGP, in osteoblasts. 8 …”
Section: Osteocalcin and Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, confirmation through changes in multiple bone formation markers would be consistent with the known effects of insulin on the osteoblast. 12 In fact, in mice, insulin signalling stimulates the synthesis not only of osteocalcin but also of other major matrix proteins, as well as MGP, in osteoblasts. 8 …”
Section: Osteocalcin and Glucose Metabolismmentioning
confidence: 99%
“…The most surprising finding was that only the uncarboxylated or undercarboxylated forms of osteocalcin were active. 5-12 Since those reports, a growing number of studies have linked serum osteocalcin concentrations to glucose homeostasis in humans. This research has led to speculation that serum osteocalcin concentrations have clinical utility as a risk marker for diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Serum osteocalcin was negatively correlated with fasting insulin and ‘homeostasis model assessment of insulin resistance’ [34]. Several other reports link high osteocalcin levels to insulin sensitivity [31], but studies in humans have not yet shown direct causal effects [35]. Nevertheless, these studies indicate that osteocalcin supports insulin function and thus storage of energy-rich fuels in adipose tissue and muscle.…”
Section: Energy Storage Hormonesmentioning
confidence: 99%
“…The effect of insulin on bone mineral content and on bone strength is difficult to determine as the insulin resistance status of the patient plays a large role in whether insulin has an effect or not. 41 It has proven quite difficult to separate the direct and indirect effects of insulin on bone.…”
Section: Discussionmentioning
confidence: 99%